Frequency-sweep linearization for FMCW sensors with high measurement rate - Pichler, Markus; Stelzer, Andreas; Gulden, Peter; Seisenberger, Claus; Vossiek, Martin (IEEE/MTT-S International Microwave Symposium Digest, 2005)
In certain object surface distance measurement applications where contactless and robust estimates are required, microwave frequency modulated continuous wave sensors are the solution of choice. High linearity of transmitted frequency over time is a prerequisite for accurate results and poses a challenge, if high measurement rates are to be achieved simultaneously. This paper presents a novel method for sweep linearization in phase-locked-loop-based frequency synthesizers by determining the instantaneous output signal phase and -error directly within the synthesizer. The proposed method is compared to a conventional voltage predistortion linearization technique. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.freque
Keywords: Chirp radar; Frequency synthesizers; Phase locked loops; Phase measurement